Bulk-Fill Composite Restorations Step-by-Step Description of Clinical Restorative Techniques Case Reports - Vasconcelos Monteiro DDS, MS, PhD Studen, Renata (2019)
Composite resins are excellent materials for direct restorations in the posterior region, satisfactorily reestablishing esthetics and function. Recently, a new class of composites has been commercialized, the so-called Bulk-fill resins. These resins may be inserted in the dental cavity in increments of 4 to 5 mm thick, and have the advantages of reducing polymerization shrinkage and clinical working time. The aim of this case report was to describe the use of bulk-fill composite resins to restore Class I and Class II cavities by means of two different restorative techniques.